New Fisheries-related data from the Mediterranean Sea (April 2015) - KARACHLE, P.K.; BAŞUSTA, A.; BAŞUSTA, N.; BOSTANCI, D.; BUZ, K.; GIRGIN, H.; CHATER, I.; KOKOKIRIS, L.; KONTAŞ, S.; KTARI, M.-H.; MARAVELIAS, C.D.; MINOS, G.; et al. (Mediterranean Marine Science, 2015)
In this second Collective Article with fisheries-related data from the Mediterranean Sea we present the evaluation of bony structures in aging of Barbus tauricus, otolith dimensions-body length relationships for two species (Trachinus draco and Synchiropus phaeton), information on the growth of juvenile Thunnus thynnus and of Ruvettus pretiosus, weight-length relationships for three species (Aulopus fiamentosus, Thunnus thynnus and Tylosurus acus imperialis) and data on feeding habits and reproduction of Aulopus fiamentosus.